A case of musical hallucinations induced by tramadol - Tatsu Hase; Norio Yasui‐Furukori; Shigeki Yamaguchi; Kazutaka Shimoda (Wiley, 2023)
Abstract Aim Although tramadol has been suggested to have a higher risk of producing hallucinations than other opioids, reports of musical hallucinations are extremely rare. Case Presentation A 72‐year‐old woman came to our department complaining of auditory hallucinations. She had been diagnosed with lumbar spinal canal stenosis associated with herniated and slipped disks. Due to persistent back pain, tramadol was started, and the dose was increased to 300 mg/day. The next day, she began to hear nursery rhymes, songs of the Ministry of Education, and folk songs. The musical auditory hallucinations disappeared with the use of antipsychotics and the discontinuation of tramadol. No relapse of musical auditory hallucinations was observed after the discontinuation of antipsychotics. Conclusion Based on the clinical course, we concluded that the auditory hallucinations were musical hallucinations induced by tramadol.